Analysing the sovereignty claim by Philippine over Sabah / Mohamad Muaawiz Abu Bakar Mohamad Zul and Firdaus Misti - Mohamad Zul, Mohamad Muaawiz Abu Bakar; Misti, Firdaus (2013)
Lahad Datu 'standoff incident has re-trigger the debates on the sovereignty of Sabah that once started in the 60's. Philippine first claim for Sabah on June 22nd 1962 during the reign of Macapagal and since that day, no treaty has been sign by both parties to resolve this issue. The early 60's marks as the beginning of unstable diplomatic relationship between these two neighbours. Therefore, this study is conducted to analyse the sovereignty claim by Philippine over Sabah thru library research. It is important to examine the claim in order to find the main ground of the claim before Malaysia can take any further action in respond to it. Philippine claim are based on two main ground; Historical and legal basis. Philippine's main grounds are first, based on the Cession 1878 Agreement between Overbeck & Dent and the Sultan of Sulu, where both parties have a different interpretation to the meaning of the word 'Padjak' in the agreement. Philippine interpret it as 'lease' while Malaysia interpret it as 'cession'. Second ground in Philippine claim is that Spain who inherit the sovereignty of Sulu Sultanate over its jurisdiction did not relinquish her right to claim for North Borneo who at the time, under the administration of British in 1885 Madrid Protocol between the foreign powers in the region. The third ground in Philippine claim is that, the act of self-determination exercised by the people of Sabah to form the Federation of Malaysia in not valid as the Cobbold Commission merely an inquiry to ask the opinion of the inhabitants in Sabah not a referendum to a self-determination. This however denied by United Nations after examining the outcome of the Cobbold Commission and representatives of UN was sent to Sabah. In conclusion, Philippine's ground for claim over sovereignty of Sabah are not relevant as they are contradict or overlapped by the treaties and International Law. However, Philippine so determine to claim Sabah. This dispute can only be resolved when both parties, agree to resolve the claim via treaty or the other relevant option is by bringing this matter to the International Court of Justice. Until both parties have the agreement, Malaysia is deemed to hold the sovereignty over Sabah.